Nghiên cứu sinh tổng hợp poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) của chủng vi khuẩn MT33 phân lập từ nước thải - Phong, Trần Hữu; Thanh Nga, Bùi Thị; Thanh, Phan Duệ; Thược, Đoàn Văn (Vietnam Journal of Science and Technology, 2015)
Twenty PHA producer bacteria were isolated and screened from waste water collected from Mach Trang village, Dong Anh district, Ha Noi city. Among them, the highest PHA producer bacterium – strain MT33 was chosen for further study. Strain MT33 is a gram-positive and rod-shape bacterium, able to produce poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) with 3% mol HV unit. The optimum conditions for cell growth and PHBV production by strain MT33 are glucose of 20 g/L, yeast extract of 3 g/L, pH 5,5-7, and temperature 30-32oC. Maximum CDW and PHBV content of 5,08 g/L and 67% were respectively obtained by strain MT33 after 36 h of cultivation at optimal condition.